Contaminated in-house environment contributes to the persistence and transmission of NDM-producing bacteria in a Chinese poultry farm. (June 2020) - Zhai, Ruidong; Fu, Bo; Shi, Xiaomin; Sun, Chengtao; Liu, Zhihai; Wang, Shaolin; Shen, Zhangqi; Walsh, Timothy R.; Cai, Chang; Wang, Yang; Wu, Congming
Highlights: Up to 18% of 1-day-old chicks contaminated with bla NDM within 24 h in grow-out farm. Novel NDM-like-metallo-β-lactamase gene, bla NLM was identified in Pseudomonas putida . IncX3 plasmid account for 71% of bla NDM carriage and persist in farm over 16 months. Over 20% NDM-producing isolates carry either colistin resistance gene mcr-1 or mcr-8 . Long vacancy period and disinfection procedure fail to eliminate bla NDM in farm. Abstract: While carbapenem use is prohibited in the poultry production chain and carbapenem-resistant Enterobacteriaceae (CRE) are absent from hatchery farms, New Delhi metallo-β-lactamase-producing CRE contamination of commercial broiler chicken farms (grow-out farms) can occur via living hosts such as flies. However, it is not known whether the inanimate factors from in-house environment play a role in the persistence of CRE on commercial farms. Herein, we monitored one typical broiler house in Hebei Province, China, from January 2017 to April 2018. We collected 350 cloacal samples from four broiler batches along with 582 environmental samples (194 in the raising period and 388 in the vacancy period) from sites including the surfaces of drooping boards, feeding troughs, nipple drinkers, corridor floors, sewage trenches, and air. All samples were screened for bla NDM and cultured for NDM-producing isolates. The resistance profiles, genotypes, and genetic context of bla NDM in CRE isolates were further characterized. Results showed that 1-day-old broilers, which were transferred from a hatchery farm and negative for CRE, acquired bla NDM within 24 h of transfer (2 days of age), with a detection rate of up to 18.6%. High bla NDM detection rates (26.8%–31.4%) were obtained among all environmental samples except air after standard cleaning and disinfection during the vacancy period. bla NDM carriage rates (52.9%–72.9%) within the flocks remain stable and high across the next three broiler batches. Overall, 279 NDM-producing bacteria, including 259 Enterobacteriaceae (8 species), 14 Morganellaceae (3 species), three Alcaligenes faecalis and three Pseudomonas putida isolates, were recovered from 85 (24.3%) cloacal and 101 (17.4%) environmental samples. Three NDM variants, including NDM-5 ( n = 181), NDM-1 ( n = 92), and NDM-9 ( n = 3), and a novel NDM-like-metallo-β-lactamase (NLM, n = 3) were identified among the samples. The predominant NDM-producing CRE species among the samples were Klebsiella pneumoniae (CRKP; 32.6%, n = 91) and Escherichia coli (CREC; 27.2%, n = 76). Both clonal and horizontal transmission of bla NDM and an overlap of sequence types (STs) were observed in both CREC and CRKP from chicken and environmental samples. Notably, ST6751 CREC and ST37 CRKP persisted throughout the 16-month surveillance period. IncX3 ( n = 197, 7 species), IncA/C2 ( n = 41, 5 species), and IncFII ( n = 8, E. coli ) were the three major bla NDM -carrying plasmid types among the isolates . Although routine cleaning and disinfection procedures and "all-in/all-out" management were performed, once introduced to the farm environment, a diverse range of NDM-positive isolates may survive and persist, becoming an important reservoir of NDM-positive CRE for broiler chickens. Therefore, cleaning and disinfection procedures should be improved on poultry farms to avoid cross-contamination of NDM-producing bacteria between different batches of chickens, as well as further downstream in the poultry production chain.